Question:
A translation is applied to the triangle where A(1, 4) , B(2, -2) , and C(-3, 2). The image is the triangle that has vertices A′(5, 4) , B′(6, -2) , and C′(1, 2).
Answer:
[tex](x,y) ==>[/tex] [tex](x + 4,y)[/tex]
Step-by-step explanation:
Given
[tex]A = (1,4)\\B = (2,-2)\\C = (-3,2)[/tex]
[tex]A' = (5,4)\\B' = (6,-2)\\C' = (1,2)[/tex]
From the translation of triangle ABC to A'B'C',
It will be observed that the y coordinates of both triangle remain unchanged.
This implies that triangle ABC is translated on the x coordinates alone.
Considering the x coordinates of A and A', we have:
[tex]1 + k = 5[/tex]
Make k the subject
[tex]k = 5 - 1[/tex]
[tex]k = 4[/tex]
When 4 is added to the x coordinates of B and C, it gives the x coordinates of B' and C'.
Hence, the rule of translation is:
[tex](x,y) ==>[/tex] [tex](x + 4,y)[/tex]